Implementing the Communicative Language Teaching (CLT) Approach to Enhance Speaking Ability of Grade VIII Students at SMP Negeri 3 Padangsidimpuan - Munthe, Aprilia Enjelika; Huda, Rahmat; Khairunnisah; Sormin, Ayunda Sabrina; Ambarita, Rosmita; Akhmad Tarmizi; Muhsin; Awae, Salma (jurnalalfa, 2025)
The goal of the study was to help students become more confident public speakers. The objective is to investigate the efficacy of the Communicative Language Teaching (CLT) technique in enhancing speaking skills among students at SMPN 3 Padangsidimpuan. Communicative Language Teaching (CLT) is a pedagogical approach that prioritizes communication as the primary objective of language acquisition. This study employs classroom action research, encompassing planning, action, observation, and reflection. The data were acquired by observations, reflections, documentation, and assessments (pre-test and post-test). The implementation of the Communicative Language Teaching (CLT) technique during the initial cycle demonstrated a gradual enhancement in the students' English speaking proficiency. Improvements were implemented during the learning process in the second cycle. In this second cycle, the English speaking proficiency of grade VIII-1 students improved through the application of the Communicative Language Teaching (CLT) technique across both cycles. The implementation of the Communicative Language Teaching (CLT) technique enhances vocabulary mastering among Grade VIII-1 students at SMPN 3 Padangsidimpuan.